From Behaviorism to Neoconstructivism: A Review of Educational Theories for the Development of Independence in the Conditions of Destruction - Yulia N. Koreshnikova; Pavel S. Sorokin (Вопросы образования)
An increasing number of cases have revealed that previously stable systems have shown attitudes towards unstable ones, not only generating risks, but also showing opportunities for manifestation in the manifestation of new communities and manifestations of action. There is a growing demand for agency, as an independent existence of the totality. In order to determine how adequately the institution responds to this demand today (and may be likely in the future) of the key human development, the formal education system, it is important to take into account key educational theories that take into account the logic of the development of an initiative in the field of education. This article provides a review and analysis of the capture and recognized classical educational theories (learning theory) of behaviorism, cognitivism and constructivism regarding their opposites for solving the problems of developing abilities for independent creative action (agency). The outcomes that are most relevant to the development of agency are constructivist theory, in which the learner is given an active role in the exploration of outcomes. But this theory also has significant requirements, since the focus is on learning cognitive abilities - knowledge and feelings that reproduce the flesh of the flesh given from the outside, and not the ability to develop an independent creative action that maintains and improves the social world (including the creation of communities or institutions). The authors attempted to formulate possible grounds for a new educational theory - neo-construction, which emphasizes the ability for independent creative action as a key educational result, and also takes into account a number of achievements of cognitivism and behaviorism, which are influenced by the interpretations of constructivism.